Immunization related behaviour among healthcare workers in Europe: Results of the HProImmune survey - Karnaki, Pania; Baka, Agoritsa; Petralias, Athanassios; Veloudaki, Afroditi; Zota, Dina; Linos, Athena; HProImmune Partnership (Central European journal of public health, 2019)
OBJECTIVES: Vaccine preventable diseases (VPDs) continue to pose a significant threat to healthcare workers (HCWs) while immunization among this group remains low. HCWs' behaviours as well as facilitators and barriers towards their vaccination for a number of VPDs were explored through an EU-wide survey. METHODS: HCWs across the EU answered online survey that explored attitudes and behaviours towards vaccination for a number of VPDs. Response data were adjusted based on weights estimated by HCWs' country and working profession according to WHO statistics. The survey was delivered between October 2012 and April 2014. RESULTS: Analysis was based on responses from 5,424 HCWs from 14 European countries. The majority (86.7%) had a positive attitude regarding immunizations. HCWs considered influenza (86.4%), viral hepatitis type B (71.9%) and tuberculosis (59.1%) as higher risk diseases for occupational exposure in the workplace. However, 43.8% reported not receiving a seasonal influenza vaccine in the last 10 years and 65.6% reported not receiving the pandemic influenza vaccine in 2009. Main enablers towards immunizations included believing in vaccine protection and easy, free of charge access to vaccines in the workplace. Barriers to up-to-date immunizations differed according to disease but included concerns about short- and long-term effects. CONCLUSION: Although the concept of mandatory vaccination seems to be favoured by many health professionals in Europe, it remains a controversial subject both among HCWs' profession categories and also among different countries. Interventions to increase vaccination among HCWs would benefit by tailoring their approach according to disease and target group.
Keywords: imunizace; healthcare workers; vakcíny proti chřipce; průzkumy a dotazníky; Surveys and Questionnaires; vakcinace; Evropa; Health Personnel; immunization; Immunization; lidé; vaccines; Humans; Vaccination; zdravotnický personál; Influenza Vaccines; Europe